2020
DOI: 10.1371/journal.pone.0235493
|View full text |Cite
|
Sign up to set email alerts
|

Impact of brain natriuretic peptide reduction on the worsening renal function in patients with acute heart failure

Abstract: The prognostic impact of worsening renal function (WRF) in patients with acute heart failure (AHF) remains under debate. Successful decongestion might offset the negative impact of WRF, but little is known about indicators of successful decongestion in the very acute phase of AHF. We hypothesized that decongestion as evaluated by the percent reduction in brain natriuretic peptide (BNP) could identify relevant prognostic implications of WRF in the very acute phase of AHF. Methods and results Data on 907 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Previous studies found that WRF with higher BNP levels at discharge had a worse prognosis ( 32 , 33 ). This study further found that regardless of the degree of WRF, 1-year mortality was higher in patients with higher BNP levels at discharge.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies found that WRF with higher BNP levels at discharge had a worse prognosis ( 32 , 33 ). This study further found that regardless of the degree of WRF, 1-year mortality was higher in patients with higher BNP levels at discharge.…”
Section: Discussionmentioning
confidence: 89%
“…[29] The implications of WRF during the early phase of AHF can be better understood by evaluating the decongestion process (measured as the percentage drop in BNP concentration). [30] A percentage decrease of ≥30% in BNP levels when compared to admission values was shown to be associated with favorable outcomes, both during the hospital stay and at 1 year follow-up. [31,32] A combination of BNP ≥ 250 pg/mL, occurrence of in-hospital WRF, and history of hospital admission for heart failure predicted composite outcomes (short-term and long-term cardiovascular mortality).…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate Cox regression models were reconstructed to evaluate the prognostic value of FIB‐4 to predict mortality when compared with other variables only in the WRF group. We adjusted the model for BUN, eGFR, and change in per cent BNP, which have been reported as useful markers to identify prognostically relevant WRF (Model 1) 8,19 . Model 2 was adjusted by adding the variables used in Model 1 to those used in the multivariate analysis of the primary endpoint.…”
Section: Methodsmentioning
confidence: 99%
“…We calculated Pearson's correlation coefficient to evaluate the relationship between the log‐transformed FIB‐4 score at discharge and the following indicators of congestion: log‐transformed BNP at discharge; estimated plasma volume status (ePVS) at discharge calculated using the Strauss formula 18 ; changes in total protein, serum albumin, haemoglobin, haematocrit, 10 and ePVS; and log‐transformed change in per cent BNP from admission to discharge. 19 Multivariate Cox regression models were reconstructed to evaluate the prognostic value of FIB‐4 to predict mortality when compared with other variables only in the WRF group. We adjusted the model for BUN, eGFR, and change in per cent BNP, which have been reported as useful markers to identify prognostically relevant WRF (Model 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation